The German Communities That Care Youth Survey: dimensionality and validity of risk factors - Reder, Maren; Runge, Ronja A.; Schlüter, Helge; Soellner, Renate (Frontiers in Public Health, 2024)
Background: Communities That Care (CTC) is an evidence-based community change strategy for supporting healthy youth development. One of its key elements is the development of a community profile to identify and prioritize risk factors for health and behavioral problems in adolescents based on the CTC Youth Survey. The strategy was originally developed and evaluated in the USA. An adapted version of the survey has been used in Germany since its first implementation in 2008. However, the dimensionality and validity of the adapted risk factor scales have not yet been evaluated. Therefore, this study aimed to confirm the assumed unidimensional structure and to establish the concurrent criterion validity of each risk factor. Methods: A sample of 1,911 adolescents attending grades six to eleven in Lower-Saxony, Germany, was used to evaluate 23 risk factor scales of the German CTC Youth Survey covering the domains peer/individual, family, school, and community. Confirmatory factor analysis was used to assess the dimensional structure of all risk factors with sufficient item numbers. Goodness of fit was determined using CFI, SRMR, and RMSEA. Latent regression analysis tested the concurrent criterion validity of all unidimensional risk factors. For this, violent and delinquent behaviour, substance use, and depressive symptomatology were regressed on each risk factor. Results: All evaluable risk factors demonstrated acceptable to good model fit regarding unidimensionality and predicted violent and delinquent behaviour, and substance use better than depressive symptomatology. Regarding the peer/individual risk factors, there are particularly high correlations with violent and delinquent behaviour, and substance use. In contrast, two risk factors were not correlated with substance use, while two other risk factors were not correlated with depressive symptomatology. Conclusions: Overall, the results indicate that most risk factors demonstrate unidimensionality and are valid in terms of concurrent criterion validity. Although some risk factors were not correlated with every outcome, they still predicted most outcomes, suggesting that the CTC Youth Survey is a viable tool for communities to assess their community risk profile. Risk factors that did not demonstrate unidimensionality or concurrent criterion validity should be monitored in future surveys and interpreted with caution until further evidence is available.